2016
DOI: 10.1002/hbm.23254
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical myelination in musicians with absolute pitch: Quantitative morphometry using 7‐T MRI

Abstract: Absolute pitch (AP) is known as the ability to recognize and label the pitch chroma of a given tone without external reference. Known brain structures and functions related to AP are mainly of macroscopic aspects. To shed light on the underlying neural mechanism of AP, we investigated the intracortical myeloarchitecture in musicians with and without AP using the quantitative mapping of the longitudinal relaxation rates with ultra‐high‐field magnetic resonance imaging at 7 T. We found greater intracortical myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 101 publications
3
50
0
2
Order By: Relevance
“…In our previous study [Kim and Knösche, ], we found a positive correlation between the APS and the cortical myelin content in the right PP. In the current study, we hypothesized a positive relationship between the APS and RSFC of the right PP to a number of cortical areas.…”
Section: Methodsmentioning
confidence: 63%
See 4 more Smart Citations
“…In our previous study [Kim and Knösche, ], we found a positive correlation between the APS and the cortical myelin content in the right PP. In the current study, we hypothesized a positive relationship between the APS and RSFC of the right PP to a number of cortical areas.…”
Section: Methodsmentioning
confidence: 63%
“…Of most relevance in the present context, Warren and colleagues demonstrated higher sensitivity to pitch chroma in the PP and higher sensitivity to pitch height in the PT [Warren et al, ]. As mentioned above, the processing of pitch chroma is the essential characteristic of AP [Deutsch, ; Deutsch and Henthorn, ; Kim and Knösche, ; Miyazaki, ; Takeuchi and Hulse, ], which speaks for a specific involvement of the ventral pathway in AP perception, most probably in the early perceptual process. This has been corroborated by the finding of increased intra‐cortical myelination in the right PP of AP possessors [Kim and Knösche, ].…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations